2011
DOI: 10.1590/s0100-29452011005000044
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de progênies e genitores de pessegueiro com base nas características dos frutos

Abstract: Melhorar a qualidade do fruto é um dos principais objetivos dos programas de melhoramento genético do pessegueiro, tendo relação direta com as preferências de mercado e do consumidor. Quando se fala em qualidade, busca-se obter plantas produtivas, com frutos grandes e firmes, com ótimos sabor e coloração. Porém, o pêssego produzido no Brasil ainda deixa a desejar, principalmente em firmeza, quando comparado aos padrões internacionais. Os objetivos deste trabalho foram avaliar, selecionar e indicar genótipos qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
1
0
4
Order By: Relevance
“…The RRB was, on average, 59.53% in 2014 and 71.54% in 2015, demonstrating that there was a greater amount of chill available to the cultivars to overcome dormancy in the second year (Table 2). These values demonstrate a good budburst rate, as other authors regard 50% as a good rate of budburst for peach plants (Raseira & Nakasu, 1998;Wagner Júnior, Bruckner, Cantín, Sánchez, & Santos, 2011). Wagner Júnior et al (2009 studied the behaviour of peach tree cultivars and concluded that the greater chill accumulation also provides a gradual increase in budburst percentage.…”
Section: Resultssupporting
confidence: 70%
“…The RRB was, on average, 59.53% in 2014 and 71.54% in 2015, demonstrating that there was a greater amount of chill available to the cultivars to overcome dormancy in the second year (Table 2). These values demonstrate a good budburst rate, as other authors regard 50% as a good rate of budburst for peach plants (Raseira & Nakasu, 1998;Wagner Júnior, Bruckner, Cantín, Sánchez, & Santos, 2011). Wagner Júnior et al (2009 studied the behaviour of peach tree cultivars and concluded that the greater chill accumulation also provides a gradual increase in budburst percentage.…”
Section: Resultssupporting
confidence: 70%
“…Wagner Júnior et al (2011), avaliando 17 populações de pessegueiro, relataram que a firmeza da polpa variou de 3,2 a 7,8 libras e a percentagem de vermelho da epiderme de 56,9 a 96,0%, variação bem menor do que a encontrada neste trabalho (Tabela 3). Houve correlação significativa entre algumas caracterís-ticas em estudo (Tabela 5).…”
Section: Resultsunclassified
“…A região Sudeste do Brasil apresenta boas condições para a exploração econômica de fruteiras de clima temperado, devido principalmente à elevada altitude (Wagner Júnior et al, 2011). O Brasil produziu na safra 2013, 217.706 toneladas.…”
Section: O Pêssego é Uma Fruta Climatérica De Clima Temperado Pertencunclassified